Maize and cowpea intercropping plant density under irrigation condition - Cardoso, Milton José; Filho, Francisco Rodrigues Freire; Ribeiro, Valdenir Queiroz; Frota, Antonio Boris; Melo, Francisco de Brito (Pesquisa Agropecuaria Brasileira, 1993)
The productive performance of maize (Zea mays) and cowpea (Vigna unguiculata) intercropped system under sprinkle irrigation condition was evaluated in Teresina, PI, Brazil. The maize and cowpea crops were planted simultaneously at the same row, with three populations of maize (20, 40 and 80 thousand plants/ha), and four populations of cowpea (30, 60, 90 and 120 thousand plants/ha), combined in a factorial schedule (3 x 4) in randomized blocks with five replications. After the maize earing stage the cowpea was harvested, and one second cowpea crop was planted. On this phase one cowpea row was planted between two maize rows, with six cowpea plants by square meter. There was a linear increasing on the maize grain yield when the plant number by area increased showing the possibility to cropping cowpea twice at the same area without any failure in a maize productivity. There was a linear increasing on the cowpea grain yield when the maize plant by area decreased.
Keywords: Zea mays; Vigna unguiculata; plant spacial arrangement